Mykola Kuryliuk’s astronautical painting or the sidereal aesthetics of Major Tom - Tillería Aqueveque, Leopoldo (2025)
The essay addresses the pictorial work of the contemporary Ukrainian artist Mykola Kuryliuk through the commentary on two of his most recent acrylics: Augmented reality 73 and Augmented reality 100, both from 2023. The objective of the research is to establish in what sense the pop- Kuryliuk’s aesthetic, whose icon is undoubtedly the astronauts, could be interpreted, in the midst of post-postmodernism, as beautiful art and what would be the keys to this consideration. To do this, Kant’s aesthetic perspective and several updated publications on contemporary art are used as a theoretical foundation. Finally, what is seen in Kuryliuk’s works, and that is what has been meant with the concept of pop-aesthetics and with the allusion to a style that randomly mixes surreal and pastel tones, but also remains of lampoons, the date of man’s first step on the Moon and a hypothetical cover of VOGUE, and, all this, in front of sidereal space, is that such ramblings of the imagination about the beauty in nature, can be extended to all the beauty in the art. And this is precisely the activity of artistic genius: the proportion of a universal order that makes such beauty possible.